2015
DOI: 10.1074/jbc.m115.669481
|View full text |Cite
|
Sign up to set email alerts
|

Direct Melanoma Cell Contact Induces Stromal Cell Autocrine Prostaglandin E2-EP4 Receptor Signaling That Drives Tumor Growth, Angiogenesis, and Metastasis

Abstract: Background: Prostaglandin E 2 (PGE 2 ) is an inflammatory mediator produced in cancer. Results: B16 melanoma cells injected into mice metastasized to bone and soft tissues by activating PGE 2 -EP4 signaling in stromal cells, inducing osteoclast activation, angiogenesis, and cancer cell proliferation. Conclusion: Stromal cell PGE 2 is a key mediator of melanoma tumorigenesis and metastasis. Significance: EP4 receptor blockade is a new potential therapy for tumor metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…However, injection of B16F10 melanoma cells into left ventricle resulted in macroscopically recognizable metastasis in bones, ovaries, adrenal glands, and brain at days 12-17 (Jones et al 2006). Our melanoma subline also exhibits a similar metastasis in systemic organs additionally including lungs, liver, and kidney but rarely in brain and muscle (Inada et al 2015). Taken together, if metastatic process includes primary tumor-led preselection or precultivation of the target organ or soil in the total absence of tumor cells or seed in the tissue, then this should be called premetastatic organ.…”
Section: Llc B16mentioning
confidence: 56%
“…However, injection of B16F10 melanoma cells into left ventricle resulted in macroscopically recognizable metastasis in bones, ovaries, adrenal glands, and brain at days 12-17 (Jones et al 2006). Our melanoma subline also exhibits a similar metastasis in systemic organs additionally including lungs, liver, and kidney but rarely in brain and muscle (Inada et al 2015). Taken together, if metastatic process includes primary tumor-led preselection or precultivation of the target organ or soil in the total absence of tumor cells or seed in the tissue, then this should be called premetastatic organ.…”
Section: Llc B16mentioning
confidence: 56%
“…Inada et al reported that the VEGF-A secretion from the CAFs within melanoma xenografts was enhanced by PGE2 and this enhancement was significantly suppressed by an EP4 antagonist, which suggest that PGE2-EP4 signaling plays an important role in the secretion of VEGF-A from CAFs [60].…”
Section: Fibroblastsmentioning
confidence: 99%
“…The BMD was calculated by dividing the bone mineral content of the measured area by the area. CT scanning of the tibiae and calvariae was performed using a microfocus x-ray CT system (R_mCT2; Rigaku and SMX-90T; Shimadzu), and three-dimensional microstructural image data were reconstructed using the software program as reported previously (17).…”
Section: Differentiation Of Bone Marrow Macrophages Into Pre-osteoclamentioning
confidence: 99%
“…They suggested the possible effectiveness of cabozantinib in both soft tissues and bone sites, but the modulation of bone remodeling by the kinase inhibitor has not been studied. In our previous studies using mouse malignant melanoma B16 and human breast cancer MDA231, we have shown that cell-cell interactions between cancer cells and host osteoblasts could induce RANKL expression in osteoblasts and elicit osteoclastic differentiation and severe bone destruction in the metastatic sites (17,18). We therefore decided to examine the effects of MET/VEGFR kinase inhibitors on host cells such as osteoblasts and osteoclasts to define the possible role of these kinases in the bone phenotype associated with prostate cancer.…”
mentioning
confidence: 99%